The energetic costs of nest building in birds. (1st March 2013) - Mainwaring, Mark; Hartley, Ian
Parental investment in reproduction is generally limited by the availability of food and so avian life-history research has generally focused on the brood rearing phase, when food requirements are greatest. Only relatively recently has the focus extended to the incubation phase and, even more recently, to the nest-building phase where there is now observational, comparative and experimental evidence that avian nest building is an energetically and temporally expensive activity. This review emphasises that nest construction is energetically expensive and we suggest that such costs should be incorporated into avian life-history research.